Reducing food waste in food manufacturing companies. (20th November 2016) - Garrone, Paola; Melacini, Marco; Perego, Alessandro; Sert, Sedef
Abstract: Putting unsold food at good use is clearly a high-priority option according to the Food Waste Hierarchy, but we still know relatively little about the antecedents, strategies, and processes that make it possible within companies. This paper aims at explaining how food manufacturers can prevent the degradation of generated surplus food into waste. Based on an extensive literature review and 4 exploratory case studies, research questions are formulated about (i) available avenues for managing surplus food, and (ii) internal drivers that make these avenues viable and efficient. In order to adapt, refine and corroborate the conceptual framework, the research conducts 10 descriptive case studies of Italian food manufacturers. Results from the cross-case analysis highlight the multiplicity of reuse and redistribution options, and their viability over the product shelf life. The analysis also shows that a structured surplus food control system and partnerships with food aid organizations are necessary to reduce food waste. Highlights: A framework to reduce food waste is developed for food manufacturing. Multiple options to reuse and redistribute unsold products are presented. Dynamic criteria to choose among surplus food management options are identified. Measurement, planning and inter-function coordination are shown to be crucial. Managing partnerships with food aid organizations is a critical success factor.